Influence of inorganic fillers on the structural and transport properties of mixed matrix membranes - Lua, Aik Chong. (2013)
In this study, three types of inorganic fillers—fumed nano-SiO2, synthesized mesoporous MCM-41, and zeolite 4A—were incorporated into P84 matrix to prepare mixed matrix membranes. The structural characteristics and transport properties of the resulting composite membranes were investigated. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the dispersion of the filler particles in the composite membranes. TEM micrographs verified that there were no nonselective pores at the particle–polymer interfaces of the composite membranes. Differential scanning calorimetry tests were conducted to investigate the structure of the composite membranes. The glass transition temperatures (Tg) of the P84/MCM-41 and P84/4A composite membranes were 11 and 30°C, respectively, above that of pure P84 membrane. But, the Tg value for the P84/SiO2 composite membrane decreased by 22°C when compared with that of the P84 membrane. The density of the composite membrane was also measured to calculate its fractional free volume. Gas permeation tests showed that, among the three synthesized composite membranes, the P84/SiO2 membrane had the best performance in terms of gas separation. P84/SiO2 membrane exhibited 20, 63, 59, and 45% increases in the permeabilities of He, O2, N2, and CO2, respectively, above those for the P84 membrane whilst maintaining comparable good selectivities.